Sosialisasi Dan Implementasi Aplikasi Edmodo Sebagai Media Pembelajaran Online di MasaPandemic Corona virus Disease 2019 (Covid-19) - Nur Kumala Dewi; Arman Syah Putra (Tekinfo: Jurnal Bidang Teknik Industri dan Teknik Informatika, 2020)
The background of this research is how the authors continue to carry out learning and teaching activities during the Pandemic Coronavirus Disease 2019 (Covid-19), when Large-Scale Social Restrictions (PSBB) all activities are carried out at home, work, study and worship are all done at home according government regulations to break the chain of Coronavirus Disease 2019 (Covid-19). The method used in this research is to conduct a literature review or literature review, by reading the journal, you will find out the current problems regarding the Pandemic Coronavirus Disease 2019 (Covid-19) and learning and teaching activities during the 2019 Pandemic Coronavirus Disease (Covid-19). ). There has been a lot of research on learning methods, but research on the application of Edmodo is still not done, this is an opportunity for the author to examine the application of Edmodo as an online learning medium. From the research, it is expected that data on the use of Edmodo will be applied to teaching and learning activities during the 2019 Pandemic Corona Virus Disease (Covid-19)